An-Nadwa Integrated Word Of Mouth Strategy in An Effort to Win Competition In Educational Institutions - Ika Maziyyatus Sholihah (Journal of Research in Educational Management, 2022)
The purpose of this research is to analyze the application of word of mouth as a marketing strategy in educational institutions to increase public interest in An-Nadwa Integrated Elementary School. This study uses a qualitative approach with a phenomenological type. Data analysis technique is done by data reduction, and followed by drawing conclusions. The results showed that word of mouth work as a marketing strategy in increasing public interest in the two institutions was carried out in three stages, namely: giving attention, interest, desire to the community about the existence of educational institutions. This research has implications for the importance of educational institutions in winning the competition.